42.6k views
0 votes
Solve each equation for k.
4k + h = -2k - 14

User Ju
by
5.3k points

2 Answers

4 votes

4k +h =-2k-14

4k+ 2k=-h-14

6k=-h-14

k=
(-h-14)/(6)

User DenMark
by
6.0k points
4 votes

4k + h = -2k - 14

  • Since we're solving for k, move all terms with k to the left side and all other terms to the right side of the equation.
  • Add 2k to both sides.

6k + h = -14

  • Subtract h from both sides.

6k = -14 - h

  • Divide both sides by 6.

k = -14/6 - h/6

  • Simplify -14/6 by dividing by 2/2.
  • -14/6 becomes -7/3, so your answer is:

k = -7/3 - h/6

User John McGehee
by
6.0k points